Analysis of the Doctrine of Ultra Vires and its Prevention Efforts Against the Actions of the Board of Directors in Limited Liability Companies - Selamat Widodo; Astika Nurul Hidayah (Faculty of Social and Political Sciences University of Bangka Belitung, 2022)
The issue of abuse of authority by company directors often occurs in companies in Indonesia. Deviations that exceed the authority of the board of directors are known as Ultra Virus. As a result of these deviations, it has the potential to cause losses to stakeholders such as shareholders, the wider community, company partners and even the company itself. In the Limited Liability Company Law, ultra virus acts can be held accountable to the Board of Directors personally, but the problem is, how the directors can fulfill the demands of the injured parties while their assets have been transferred or have been exhausted. In this writing the author uses a normative juridical approach. The result of this study is that the actions of directors who have ultra viruses have the potential to harm many parties, therefore so that these actions are not repeated there needs to be a strict supervision mechanism, because so far the supervision has only been carried out by commissioners. Internal supervision by commissioners is deemed not optimal, so it is necessary to establish by the government an institution in charge of overseeing the performance of directors in the company